Jonas Ženauskas – Soviet Prisoner of 1940–1941, Member of the July Uprising of 1941, Rescuer of Jews - Buchaveckas, Stanislovas (Genocidas ir rezistencija, 2012)
This article is mostly concerned with the biographical facts of Jonas Ženauskas, a Bolshevik prisoner of 1940-1941, anti-Soviet rebel and Jewish rescuer; these facts were mainly determined by the occupations of 1940-1944 and the Nazi Germany–Bolshevik Soviet Union war. It describes Soviet repressions, Ženauskas’ imprisonment and torture in Kaunas and NKVD prisons, as well as the liberation of prisoners on 23 June 1941. The June uprising of 1941 took place in Kaunas. Freed from prison, Ženauskas joined the uprising, armed about 50 rebels with guns, and guarded Kaunas radiophone. From August 1941 Ženauskas worked in Vilnius Criminal Police, and helped those arrested, including the Jews. He was arrested for this in 1942 by the German security police SD, and was imprisoned for seven days. As he did not regain his full health following his imprisonment in the Soviet prison, he quit the service in 1943 and returned to Kaunas. The Ženauskas family was successfully hiding 4 Jews who had escaped from the Kaunas ghetto until the end of the Nazi occupation. However, on the second day after the Red Army pushed out the German Wehrmacht, Ženauskas was arrested by the Soviet counterintelligence SMERSH. The officers of this service were not interested in the fact that he had rescued Jews, but instead accused him of non-existent crimes, and he was sentenced to death by shooting by the military tribunal (carried out on 2 March 1945). A criminal case was also initiated against his wife Sofija, and she and their two children only escaped exile by a hair’s breadth. Even during the Soviet period (1988), thanks to the efforts of his daughter Virginija Mačiulienė, as well as the two Jewish sisters saved by the Ženauskas family, Chana Lisienė and Merė Pilvinskaitė, the case was renewed. In 1989 he was vindicated. During the tragic turns of history which Lithuania and its people underwent in 1940–1944, Jonas Ženauskas, in spite of the violence inflicted on him by the Soviets, passed the human test and acting on his Christian convictions, humanistic values, assisted those persecuted, and rescued Jews, despite the death threats the Nazis had issued for such activity. Unfortunately on 2 March 2 1945, he was executed by the Bolsheviks who reoccupied Lithuania. The lives of everyone who lived through that period were shaped by the events of 1939–1944. There will never be too much historiography about them. New research, memoirs and publication of sources bring us closer to a more objective understanding of Lithuanian history, as well as an evaluation of its processes and facts both in our own country and abroad.